NOMENCLATORIAL AND SYNONYMIC NOTE ON THE GENUS ANTHAXIA (COLEOPTERA, BUPRESTIDAE) - Baiocchi, Daniele; Magnani, Gianluca (Fragmenta entomologica, 2008)
The synonymy between Anthaxia (Haplanthaxia) armeniaca Obenberger, 1929 and Anthaxia (Haplanthaxia) winkleri Obenberger, 1914 is herein established, and types, with their genitalia and original labelling, are illustrated.